Stolen billions from errant mouse clicks: Crypto requires new approaches to attack money-laundering. (4th July 2022) - Arnold, Aaron
ABSTRACT: There are two camps regarding bitcoin and other so-called "digital assets." One side sees any cryptocurrency as a financial utopia: an egalitarian technology free from centralized monetary authorities. The other sees this same technology as merely a novel mechanism for enabling more crime, corruption, and money laundering. Both positions contain an element of truth, but both share a common misapprehension: They assume that digital assets are beyond the reach of law enforcement and regulatory agencies – which is decidedly not the case, at least for now. But the digital asset economy evolves rapidly. To stay ahead of the curve, authorities will need to adapt existing rules and regulations about money-laundering, sanctions, and sending funds to rogue states – tools originally designed for an entirely different financial infrastructure – to mitigate threats to the financial system posed by virtual assets.